Implementation of Work Motivation in Improving Employee Performance at RCM Motor Workshops - Denny Lesmana; Budi Rismayadi; Neni Sumarni (Syntax Corporation Indonesia, 2023)
RCM motor repair company is one of the companies engaged in the service sector. This business activity depends on human resources, with quality human resources of course being the mainstay in the RCM motorbike repair shop, therefore the company will be able to achieve its target goals quickly and precisely. This study aims to test and find out: The effectiveness of work motivation in improving employee performance at the RCM Motor Workshop. In their activities, employees always prioritize maximum results so as to create customer satisfaction. The leader also always advises and directs all employees to always make their work a comfortable place. Based on the goals to be achieved, humans are motivated by the needs they have and that can be their motivation to produce creativity and employee abilities that can grow from the will and motivation that employees aim for. The results of the study show that work motivation has high willpower so as to create increased employee performance, it also makes employees have good performance.